The Role of Corporate Management in an Effective Crisis Management Program - Fleming, Robert S.; Zhu, Faye X. (Archives of Business Research, 2017)
Contemporary businesses face many challenges that have the potential of compromising their success and, at times, survival. These challenges include “weathering the storm” when an organization is confronted with a crisis event or situation. A crisis may originate within an organization, as in the case of a defective product, financial or legal impropriety, or a security breach compromising customer information; or from an external source, as in the case of a catastrophic weather event or labor strike impacting an organization’s operations. The importance of a proactive approach in advance of, during, and following a crisis event has demonstrated its merit in enhancing an organization’s ability to prepare for, live through, and recover from a crisis event. This paper considers the importance of a proactive crisis management program in contributing to organizational resilience to “weather the storm” of a crisis event successfully and the essential role that corporate managers play in an effective crisis management program.